PERKEMBANGAN PERMUKIMAN KUMUH LIAR (STUDI KASUS DUKUH KALISARI DESA BANYUDONO KEC. BANYUDONO KAB. BOYOLALI) - Aida Nur Azqiya; Mohammad Gamal Rindarjono; Rita Noviani (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2024)
The problem of slum organizations begins with various interrelated variables, including education level, population density level, building density level, income and poverty level. Illegal slum settlements are defined as organizations that experience a decline in housing function with illegal land ownership status or not land with Ownership Rights Status. This research aims to (1) Analyze the development of slum organizations of liars in Kalisari Hamlet, Banyudono Village, Banyudono District, Boyolali Regency in 2012, 2017 and 2022; (2) Find out the level of slum organization of liars in Kalisari Hamlet, Banyudono Village, Banyudono District, Boyolali Regency; and (3) Analyze the incidence of fraudulent slum organizations in Kalisari Hamlet, Banyudono Village, Banyudono District, Boyolali Regency. The research method used in this research is the case study method. In this research, the development of illegal slum organizations is analyzed through the development of the number of house occupants and the number of house rooms whose changes are analyzed in 2012-2017 and 2017-2022. The level of slums is determined using the 3x3x3 method, then from the level of slums the appropriate treatment can be identified based on the main problems in the slum organization area. Dukuh Kalisari developed into a fraudulent slum organization due mainly to errors in government policy, the legality of the land occupied by residents, and the condition of the organization located along the river.